2001
DOI: 10.1248/bpb.24.311
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Amentoflavone from Selaginella sinensis

Abstract: Upper respiratory infection, especially in infants and children, is a common disease worldwide. Respiratory syncytial virus (RSV) has been recognized as a major cause of such infections.1) The nucleoside analog ribavirin has been used widely for treating RSV infections in healthcare settings such as hospitals and nursing homes. However, the treatment protocol, the potentially severe side effects and the emergence of drug-resistant mutants during long-term medication with this drug have often limited its admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(67 citation statements)
references
References 12 publications
1
66
0
Order By: Relevance
“…Recently, some extracts from traditional Chinese medicinal herbs were reported to exhibit in vitro anti-RSV activity (Ma et al, 2002). A potent antiviral compound amentoflavone against RSV was isolated from the herb Selaginella sinensis (Ma et al, 2001). The result of the present study is the first report of anticancer and anti-RSV activities of Youngia japonica which is a folklore medicine used by Chinese for centuries.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, some extracts from traditional Chinese medicinal herbs were reported to exhibit in vitro anti-RSV activity (Ma et al, 2002). A potent antiviral compound amentoflavone against RSV was isolated from the herb Selaginella sinensis (Ma et al, 2001). The result of the present study is the first report of anticancer and anti-RSV activities of Youngia japonica which is a folklore medicine used by Chinese for centuries.…”
Section: Discussionmentioning
confidence: 59%
“…They are found in vegetables, fruits, seeds, fl owers as well as in wine, tea and propolis (Harborne & Williams, 2000;Grotewold, 2006 antiviral activity of flavonoids had increased in the last two decades. The most cited flavonoid classes displaying antiherpes activity are flavonols and flavones (Hayashi et al, 1997;Amaral et al, 1999;Ma et al, 2001;Chiang et al, 2003;Lyu et al, 2005;Fritz et al, 2007;Gomes et al, 2008;Schnitzler et al, 2009;Martins et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical investigations have indicated that seven biflavonoids (e.g. amentoflavone, 7 -O-methylamentoflavone, 4 ,7 -di-O-methylamentoflavone, 2,3-dihydroamentoflavone, robustaflavone, ginkgetin, hinokiflavone) [2][3][4][5][6], two flavonoids (e.g. genistin and quercetin) [2,5], lignans [7,8] and phenols [9] exist in S. sinensis.…”
Section: Introductionmentioning
confidence: 99%